2020
DOI: 10.1088/1361-6463/abc0be
|View full text |Cite
|
Sign up to set email alerts
|

Uncorrelated magnetic domains in decoupled SrFe12O19/Co hard/soft bilayers

Abstract: Composites of magnetically hard and soft phases are present in multiple and diverse applications, ranging from bulk permanent magnets in motors and generators to state-of-the-art recording media devices. The nature of the magnetic coupling between the hard and soft phases is of great technological relevance, as the macroscopic properties of the functional composite material ultimately depend on the atomic-scale interactions between phases. In this work, the hard/soft bilayer system SrFe 12 O 19 /Co has been st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…No observable difference in the H a of composites, when compared to the pure SFO, indicates that the exchange-coupling between the hard and the soft phase was not effective even though that particles were in close contact and that the size of the soft phase was within limits. This presumption is supported by the recently published paper by Soria et al [43] in which it was shown that for the effective coupling between the phases also a structural match must exist.…”
Section: Resultsmentioning
confidence: 71%
“…No observable difference in the H a of composites, when compared to the pure SFO, indicates that the exchange-coupling between the hard and the soft phase was not effective even though that particles were in close contact and that the size of the soft phase was within limits. This presumption is supported by the recently published paper by Soria et al [43] in which it was shown that for the effective coupling between the phases also a structural match must exist.…”
Section: Resultsmentioning
confidence: 71%
“…So, to effectively exchange the hard and soft magnetic phases, the particle size of the soft phase should not exceed twice that of the domain-wall width of the hard-phase material [83,88]. Some recent studies even indicated that for an efficient exchange coupling, the phases also need to have some degree of structural matching [96,97]. Furthermore, to increase the (BH) max of the composite as much as possible, the particle size of the hard phase should be at the limit of the single-domain particle size (to obtain the maximum coercivity).…”
Section: Non-ree-based Pmsmentioning
confidence: 99%
“…While recent studies have demonstrated new approaches to improve magnetic properties of hard hexaferrite powders (e.g., nanostructuring [16][17][18][19], chemical substitution [20][21][22][23], exchange spring composites [19,24,25]), manufacturing dense sintered pellets of sufficient structural integrity without degrading the optimized properties has proven a key challenge. In practice, this prevents the replacement of expensive and unsustainable REE PMs in a range of applications and is the reason why hard ferrites still generate great scientific interest [26].…”
Section: Materials For Permanent Magnets: Current Statusmentioning
confidence: 99%